2022
DOI: 10.1111/apt.16877
|View full text |Cite
|
Sign up to set email alerts
|

Letter: non‐invasive transabdominal stimulation device for the treatment of chronic constipation—proof‐of‐principle study in adults

Abstract: to take aseptic biopsies (US 20150320407 A1). B.R. Southwell was an advisor to GI Therapies (the company producing the prototype electrical stimulation device) and holds patents for electrical stimulation devices and methods. She has been funded by the Murdoch Children's

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…3). A proof-of-concept study using a tailored TENS device demonstrated improvements in symptoms and quality of life, although completion rates were low and device tolerability might be an issue [32,33]. Transabdominal interferential electrical stimulation, a varied form of TENS therapy, also demonstrated improved bowel pattern compared with sham stimulation in women with refractory constipation [34].…”
Section: Nonpharmacological Treatmentsmentioning
confidence: 99%
“…3). A proof-of-concept study using a tailored TENS device demonstrated improvements in symptoms and quality of life, although completion rates were low and device tolerability might be an issue [32,33]. Transabdominal interferential electrical stimulation, a varied form of TENS therapy, also demonstrated improved bowel pattern compared with sham stimulation in women with refractory constipation [34].…”
Section: Nonpharmacological Treatmentsmentioning
confidence: 99%
“…2 We commend Talley et al on their efforts in expanding treatment options for constipation. 3 They describe their promising experience using a non-invasive TENS device in a proof-of-principle study by treating 20 patients with chronic constipation. They found significant improvements in symptoms and quality of life, using an 8-electrode belt that delivers high-frequency, low-intensity stimulation on the abdomen, daily for 16 weeks.…”
mentioning
confidence: 99%